English use as an identity marker among Malaysian undergraduates - Wong, Fook Fei; Lee, King Siong; Lee, Su Kim; Azizah Ya'acob (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The English language, a legacy of the British colonialists, has been indelibly woven into the history of Malaysia, and because of its pervasive influence through its role in the education system, it is an important part of the identity construction of those who have gone through the system. This paper reports on the qualitative findings of a study investigating the impact of English on the sociocultural identity construction of young adult Malaysians. The data were obtained from interviews conducted with 20 Malaysian undergraduates from both public and private universities. English is one of the languages in their linguistic repertoire. The demographic composition of the respondents reflects in general the cultural and linguistic diversity of Malaysia. The paper will focus on how the use of English among these university students is perceived as an identity marker that enhances the perception of their personal and social status, and how its use may sometimes be used as the basis by members of the same ethnic community for “othering” them. The paper concludes by suggesting that since competence in the use of English is basically perceived as a form of cultural capital, a move towards enhancing English use among students within a policy that strongly advocates multilingualism is the way towards developing a more inclusive moderate sociocultural identity